Pelatihan Urban Farming Guna Meningkatkan Keterampilan Anak-Anak Panti Asuhan Tat Twam Asi - I Nyoman Indra Kumara; Decky Cipta Indrashwara; I Gede Fery Surya Tapa; Melati Budi Srikandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The urban farming training at the Tat Twam Asi Orphanage aims to enhance the skills and knowledge of children in cultivating plants in urban environments. This one-day activity employs methods that include theoretical and practical sessions. In the theoretical session, the children are introduced to the basic concepts of urban farming, including planting techniques and plant care suitable for limited spaces. The training results show that the children successfully applied the techniques they learned and demonstrated a deep understanding of the importance of urban farming in the context of food security, as evidenced by pre-test and post-test questionnaires distributed before and after the training. This program not only provides new knowledge but also fosters a sense of responsibility and environmental awareness among the orphanage children. As a recommendation, continuous training and the addition of supporting facilities could enhance the program's effectiveness in the future.